When a Seemingly Harmless Prescription Turns into Toxicity. (16th September 2018) - Azmaiparashvili, Zurab; Lo, Kevin Bryan; Habib, Nawal; Hsieh, Annie
Abstract : Valacyclovir neurotoxicity is commonly seen in the elderly and those with impaired renal function. Differential diagnosis can be challenging as a myriad of medical conditions, including herpes zoster virus associated encephalitis, may present in a similar fashion. We present a case of a 71-year-old male who presented with altered mental status in the setting of recent herpes zoster eruption. His condition was attributed to valacyclovir neurotoxicity, and initiation of appropriate supportive therapy was met with complete resolution of symptoms and normalization of cognitive function.